2008
DOI: 10.1111/j.1600-0447.2008.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of mental health services and complementary and alternative medicine in persons with common mental disorders

Abstract: The relationship between the use of CAM and mental disorders appears to vary depending on the type of mental disorder. Use of CAM seems unrelated to the use and the perceived usefulness of mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 31 publications
3
24
0
3
Order By: Relevance
“…Herbal remedies most often used for PD and other anxiety disorders in North America and Europe are single-herb preparations rather than the complex mixtures of herbs used in traditional Chinese medicine [51]. Patients are increasingly turning to CAM therapies for depression, anxiety or other mental disorders [31][32][33].The present study showed that CAM therapies may be adjunctive rather than primary therapy. Together, the popularity of CAM therapies and stigmatization of psychiatric disorders in Taiwan contribute to delaying psychiatric care.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Herbal remedies most often used for PD and other anxiety disorders in North America and Europe are single-herb preparations rather than the complex mixtures of herbs used in traditional Chinese medicine [51]. Patients are increasingly turning to CAM therapies for depression, anxiety or other mental disorders [31][32][33].The present study showed that CAM therapies may be adjunctive rather than primary therapy. Together, the popularity of CAM therapies and stigmatization of psychiatric disorders in Taiwan contribute to delaying psychiatric care.…”
Section: Discussionmentioning
confidence: 81%
“…CAM includes a broad range of health resources across all health systems, modalities, and practices; CAM therapies are generally self-defined by their users and are believed by users to prevent illness and to promote health and well-being [33]. The most common alternative therapy used by American patients is chiropractic, followed by massage therapy, herbal remedies, spiritual practices, nutritional advice, meditation, homeopathy, hypnosis, and biofeedback [44].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Not all patients with anxiety disorders benefit from conventional therapy; even under the optimum conditions of a clinical trial 20%-60% of patients will not respond to psychotherapy or anti-anxiety medications. [9][10][11][12][13] Up to one-half of patients with anxiety symptoms use complementary therapies, 14,15 sometimes provided by their physicians.…”
Section: Introductionmentioning
confidence: 99%
“…It encompasses a wide range of practices, knowledge and treatments which are not related to modern medical profession. These include massage therapy, acupuncture, chiropractic and herbal foods [1][2][3][4][5][6]. Countries in which CAM is widely used include Southeast Asia, United States, United Kingdom and Australia [7].…”
Section: Introductionmentioning
confidence: 99%